Strategy of KSPPS BMT NU Sejahtera Genuk District, Semarang City: Analysis of Problematic Financing Resolution in the Perspective of Islamic Economics - Kurniawan, Danang; Ilmih, Andi Aina (INAIFAS Press, 2024)
KSPPS BMT NU Sejahtera is an Islamic financial institution in Genuk District, Semarang City, facing problematic financing issues due to several factors. These factors include: customers closing businesses, changing the business they run, and reducing business activities due to the COVID-19 pandemic; customers being less competent in running businesses; and the decline in consumer purchasing power. Based on this analysis, we conducted research on strategies to handle problematic financing. Problematic financing collection, as part of the problematic financing handling strategy, must be carried out intensively. This is qualitative research using descriptive analysis methods. Data collection techniques include library research and field research, with data validity tests using source triangulation. After conducting research, several factors have been identified as causing problematic financing at BMT NU Sejahtera Genuk. These factors include: Internal Factors: Incompetent customers, poor management, poorly organized financial reports, poor fund usage planning, immature planning, and insufficient funds. External Factors: Changes in consumer interest, decreased purchasing power of the community, government policies, and the borrower's bad intentions.